THE APPLICATION OF CARDS IN TEACHING GRAMMAR TO IMPROVE STUDENTS WRITING SKILL: A TEACHING STRATEGY DEVELOPMENT - Eroh Muniroh (Bandar Lampung University (UBL), 2016)
This research was done to overcome the students’s problem in understanding grammar. The purpose of the research was to investigated how teaching grammar by using cards could improve students writing skill. The method of the research was classroom action research. The validity of the research used triangulation method. It lead to seek the validity of the research by collecting data from tests, observations, interview and study documents. The subject of the research was students of 7B of SMPN Satap Catang in the year of 2014/2015. The data was analyzed descriptively. The average of the tests increase from one test to the last test in each cycle. The average of pre test was 53 and It increased significantly after using cards. The average score of the first cycle was 74,The second cycle was 81.5 and 89 in the third cycle. This data showed that there was an increasing of student understanding in grammar. Based on the students writing tasks, the ability of students in writing increased significantly, in the first cycle was 70.16, in the second cycle was 79.16 and in third cycle was 86.02. The hypothesis test of Pearson Correlation showed that there was a positive correlation between students mastery in grammar and students writing ability. The observations showed the level of students participation in learning process increase significantly. Interview showed the students’ perception towards teaching grammar using cards was highly appreciated by the students. The results of this research proved that the application of cards in teaching grammar effectively improve students writing skill.